Development and Validation of a Score to Predict Mortality in Children Undergoing Extracorporeal Membrane Oxygenation for Respiratory Failure: Pediatric Pulmonary Rescue With Extracorporeal Membrane Oxygenation Prediction Score*. Issue 1 (January 2017) - Bailly, David K.; Reeder, Ron W.; Zabrocki, Luke A.; Hubbard, Anna M.; Wilkes, Jacob; Bratton, Susan L.; Thiagarajan, Ravi R.
Abstract : Objective: Our objective was to develop and validate a prognostic score for predicting mortality at the time of extracorporeal membrane oxygenation initiation for children with respiratory failure. Preextracorporeal membrane oxygenation mortality prediction is important for determining center-specific risk-adjusted outcomes and counseling families. Design: Multivariable logistic regression of a large international cohort of pediatric extracorporeal membrane oxygenation patients. Setting: Multi-institutional data. Patients: Prognostic score development: A total of 4, 352 children more than 7 days to less than 18 years old, with an initial extracorporeal membrane oxygenation run for respiratory failure reported to the Extracorporeal Life Support Organization's data registry during 2001–2013 were used for derivation (70%) and validation (30%). Bidirectional stepwise logistic regression was used to identify factors associated with mortality. Retained variables were assigned a score based on the odds of mortality with higher scores indicating greater mortality. External validation was accomplished using 2, 007 patients from the Pediatric Health Information System dataset. Interventions: None. Measurements and Main Results: The Pediatric Pulmonary Rescue with Extracorporeal Membrane Oxygenation Prediction score included mode of extracorporeal membrane oxygenation; preextracorporeal membrane oxygenation mechanical ventilation more than 14 days; preextracorporeal membrane oxygenation severity of hypoxia; primary pulmonary diagnostic categories including, asthma, aspiration, respiratory syncytial virus, sepsis-induced respiratory failure, pertussis, and "other"; and preextracorporeal membrane oxygenation comorbid conditions of cardiac arrest, cancer, renal and liver dysfunction. The area under the receiver operating characteristic curve for internal and external validation datasets were 0.69 (95% CI, 0.67–0.71) and 0.66 (95% CI, 0.63–0.69). Conclusions: Pediatric Pulmonary Rescue with Extracorporeal Membrane Oxygenation Prediction is a validated tool for predicting in-hospital mortality among children with respiratory failure receiving extracorporeal membrane oxygenation support. Abstract : Supplemental Digital Content is available in the text.